Analysis of the Professionalism of Civil Servants (PNS) In the Elementary School Development Division at the South Buru Regency Education Office - Zulfian, Zulfian; Laurens, Samson; Selanno, Hendry (Jurnal Ilmiah Global Education, 2026)
This study aims to analyze the professionalism and inhibiting factors of Civil Servants (PNS) in the Elementary School Development Division at the Education Office of South Buru Regency. The research method used is descriptive qualitative. Data were collected through interviews, observations, and documentation. The data were analyzed using the interactive qualitative data analysis model of Miles and Huberman. The results of the study show that the level of professionalism of Civil Servants in the Elementary School Development Division is generally categorized as fairly good, but not yet optimal. The inhibiting factors of employee professionalism in the Elementary School Development Division are multidimensional and originate from both internal and structural aspects of the organization. These include uneven employee discipline, unbalanced technical competencies, employee work motivation, unequal workload distribution, and weak internal supervision.